(untitled) (Global Scientific Review, 2023)
This article considers that "Avesta" is the sacred book of Zoroastrianism, which is one of the oldest religions in the world, and is an extremely important source for studying the millennia-old history, socio-economic life, culture, spirituality and values of our ancestors.